NEET during the School-to-Work Transition in the Netherlands - Alexander Dicks; Mark Levels (The Dynamics of Marginalized Youth, 2022)
This chapter investigates how individual characteristics can explain school-to-work transitions that are associated with NEET status after leaving secondary school in the Netherlands. The Netherlands is a particularly interesting case to study youth who are Not in Employment, Education, or Training. In 2016, the Netherlands had the lowest NEET rate in the European Union. Many Dutch institutions and policies were a deliberate attempt to counter rapidly rising youth unemployment in the 1980s, when very high rates of youth unemployment, especially among the less educated, paired with and low outflow and educational crowding out were of great concern. Track placement in secondary education is determined by the pupils' score on a series of standardised performance tests on a number of indicators and a teacher evaluation, right at the end of elementary education.
Keywords: 300